ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU TIDAK AMAN PADA PEKERJA DI DEPARTEMEN PRODUKSI PT. X - Ajeng Ayuning Mutia; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Occupational accident is 88% caused by unsafe behavior, 10% by unsafe condition and 2% by other causes. The number of unsafe behavior cases found in PT. X from 2014 to 2016, in a series are 20, 12 and 8 cases.The purpose of this study was to analyze the relationship between safety leadership, work fatigue, safety climate and job satisfaction with unsafe behavior in the Production Departement PT. X. The research type was a quantitative with cross sectional approach. The population in this research were all workers in Production Department of PT. X. The number of samples were 63 selected by stratified sampling method with proportional approach. Data collected by questionnaire. Data analysis was performed by using chi-square test. The result of statistical test showed that there were no correlation between safety leadership (p = 0,159) and work fatigue (p = 0,094) with unsafe behavior. Furthermore, there were correlation between safety climate (p = 0,000) and job satisfaction (p = 0,006) with unsafe behavior. PT. X should conduct training of safety behavior, applying reward system, assembling safety talk and safety walk, as well as assembling safety report box.